COMMUNITY COMMUNICATIONS IN ORGANIZATIONAL COMMUNICATION POLICY: Protocol aimed at territories, communities and way of life in Maranhão - Moura, Flávia de Almeida (2021)
The article presents part of an ongoing research that aims to understand the ways in which community communication fits into organizational communication policy. The study aims to present, as a final product, a Community Communication Protocol aimed at territories, communities and ways of life in Maranhão; a correlational method between theory and practice based on the particularities of this territory, thus becoming a possibility for the market to adopt and reapply. The main methodology used is design science (DS) as a possible path to applied research in Communication (SANTOS, 2018). The work is intended to contribute to the area of Community Communication by proposing to leave a Protocol as a contribution to the professional practice based on local reality.